(untitled) (Fiep Bulletin - online, 2024)
Introduction: Eating disorders are determined by several factors with high levels of complexity that are correlated and involved in the continuity of the disease. These are serious changes in eating behavior, weight and body shape causing damage to health. Among these disorders, there is vigorexia, a psychopathology in which the individual detects many defects in their self-image, leading to psychological torture. Objective: To show the psychopathological effects and characterize the eating pattern of vigorexic individuals. Methods: This is a cross-sectional study and for the preparation of the work, the most relevant information and data from the articles, course completion works, scientific journals and books on nutrition and psychology, published in the last 26 years, were selected. Results: Regarding the eating habits of these individuals, a radical change can be seen: the diet is composed of high values of proteins and low values of lipids. Food supplements rich in proteins and amino acids are widely used to develop the desired muscle hypertrophy, as well as thermogenics that are known to reduce body fat, in addition to involving the use of drugs in this process as well. Conclusion: The lack of dissemination of this type of disorder and the lack of published works on the dietary profile, requires an investigation into the occurrence of these facts for a better understanding of the problem.